James Scott correspondence - Scott, James, clergyman
Letter, signed by Scott, rector of Dettingen Parish, Prince William County, Va., written to Thomas Sherlock, Bishop of London, nominating John Brander as curate for the parish.
Clergyman.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Brander, John, -- active 1758.; Sherlock, Thomas, -- 1678-1761 -- Correspondence; Church of England -- Virginia -- Clergy; Dettingen Parish (Prince William County, Va.); Clergy